2012
DOI: 10.22230/cjc.2012v37n2a2472
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Political Consultants’ Perspectives about Political Marketing

Abstract: This research in brief explores

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Canada, though not part of Vaccari’s five-country analysis, fits within the selective influence approach. Lees-Marshment and Marland (2012) found that “Canadian political consultants are net importers of innovative tactics” (p. 340). Consultants select the best tactics for the Canadian context.…”
Section: Global Flows Of Politics Objects Of Circulation and Politimentioning
confidence: 99%
“…Canada, though not part of Vaccari’s five-country analysis, fits within the selective influence approach. Lees-Marshment and Marland (2012) found that “Canadian political consultants are net importers of innovative tactics” (p. 340). Consultants select the best tactics for the Canadian context.…”
Section: Global Flows Of Politics Objects Of Circulation and Politimentioning
confidence: 99%